Preconcentration and speciation of Cr(III) and Cr(VI) in water samples using amberlite XAD-16 resin and determination by flow injection-flame AAS - Wuilloud, Rodolfo German (2002)
A method for the pre-concentration and speciation of chromium was developed. On-line pre-concentration and determination were obtained using flame atomic absorption spectrometry (FAAS) coupled with flow injection (FI). To determine the total chromium present in water samples, the chromium species were retained on an Amberlite XAD-16 resin as chromium-4-(2-Thiazolylazo)-resorcinol (Cr-TAR) complex, at pH 5.0. On the other hand, Cr(VI) was determined by selective formation of Cr-TAR complexes with the use of 1,2 cyclohexane-diaminetetracetic acid (CDTA) as masking agent of Cr(III). The Cr-TAR complexes were formed by heating the reagents at 90?C for 50 minutes and then retained on the resin. The Cr-TAR complexes were removed from the micro-column with ethanol. The Cr(III) concentration was determined by the difference between the total chromium concentration and that of Cr(VI). A sensitivity enhancement factor of 250 was obtained with respect to the chromium determination in aqueous medium by FAAS (50 for pre-concentration and 5 due to the use of ethanol as solvent). The detection limit for the pre-concentration of 50 mL of aqueous solution was 20 ng/L. The precision for 10 replicate determinations at the 2.0-?g/L Cr level was 3.8% relative standard deviation (RSD), calculated from the peak heights obtained. The calibration graph using the separation and pre-concentration method for chromium species was linear with a correlation coefficient of 0.9994 at levels near the detection limits up to at least 100 ?g/L. The method was successfully applied to the speciation of chromium in water samples.